Talk to me how I talk: the role of African American Vernacular English in mental health diagnosis and communication - Bell, Char'dae Chanell (My University, 2025)
This qualitative study explored how African American millennial women understood their mental health diagnoses and whether language, particularly African American Vernacular English (AAVE), influenced that understanding. Guided by Critical Discourse Analysis and Critical Theory, the results demonstrate how diagnostic communication intersects with culture, language, and identity. Twelve participants were interviewed to capture their lived experiences and perspectives surrounding diagnosis comprehension. Findings revealed that participants did not receive clear explanations of their diagnoses of generalized anxiety disorder (GAD) and often had to seek understanding independently. Cultural and spiritual norms also shaped how participants interpreted their experiences and approached mental health care. The use of AAVE emerged as a culturally grounded means of expressing and making sense of these experiences. The results emphasize the importance of culturally responsive and linguistically inclusive communication to improve understanding, trust, and engagement among African American millennial women in clinical settings.
Keywords: Black women; Mental health; Anxiety disorder